MEMBANGUN KETAHANAN EKONOMI KELUARGA MELALUI PEMBERDAYAAN PEREMPUAN PEDAGANG KAKI LIMA DI KABUPATEN LUMAJANG - Muhammad Aminuddin Shofi; Muhammad Alwi Sihab Bashari ('Ibadatuna : Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to optimize the role of women in empowering the family economy of street vendors (Pedagang Kaki Lima/PKL) in Sukosari Village, Jatiroto District, Lumajang Regency. The activity is motivated by the limited participation of female PKL in economic development at the village level, despite their significant potential in supporting family economy. The method employed is counseling and mentoring with a participatory approach involving 30 participants, comprising female street vendors, wives of neighborhood heads, and PKK (Family Welfare Empowerment) administrators. The activity was conducted over four months, encompassing stages of survey, entrepreneurship counseling, and evaluation. The results demonstrated an increase in participants' understanding of the importance of women's role in family economy, enhanced motivation to develop businesses, and heightened awareness of PKL rights in legal protection. The program recommends PKL data collection by local government, facilitation of capital access through Corporate Social Responsibility (CSR) programs, and a dialogic approach in PKL enforcement and policy-making.